2005
DOI: 10.1093/nar/gki258
|View full text |Cite
|
Sign up to set email alerts
|

The SAF-box domain of chromatin protein DEK

Abstract: DEK is an abundant chromatin protein in metazoans reaching copy numbers of several millions/nucleus. Previous work has shown that human DEK, a protein of 375 amino acids, has two functional DNA-binding domains, of which one resides in a central part of the molecule and contains sequences corresponding to the scaffold attachment factor-box (SAF-box) domain as found in a growing number of nuclear proteins. Isolated SAF-box peptides (amino acids 137–187) bind weakly to DNA in solution, but when many SAF-box pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 37 publications
1
62
0
1
Order By: Relevance
“…1). 96 The SAF/SAP helix-extended loop-helix homology motif spans helices α4 and α5 of the C-terminal half. The N-terminal half, spanning (α-helices 1-3), superimposes well with the SAF/SAP motif of PIAS1, which binds double-stranded DNA (dsDNA) and might be a binding site for p53.…”
Section: 64mentioning
confidence: 99%
See 1 more Smart Citation
“…1). 96 The SAF/SAP helix-extended loop-helix homology motif spans helices α4 and α5 of the C-terminal half. The N-terminal half, spanning (α-helices 1-3), superimposes well with the SAF/SAP motif of PIAS1, which binds double-stranded DNA (dsDNA) and might be a binding site for p53.…”
Section: 64mentioning
confidence: 99%
“…These studies showed that the pseudo-SAP-SAF/SAP box, fragment 87-187, conveys preferential binding of DEK to unusual DNA structures, including supercoiled, cruciform/four-way junction or distorted DNA. 95,96 They also described its DNA-bending activity, its ability to form Despite significant knowledge derived from its biochemistry and its association with multiple cellular functions outlined above, a principle biological function of DEK remains elusive. Cytoplasmic activities for DEK are currently uncharacterized, but secreted forms of DEK that have been found in synovial fluid were implicated in triggering autoimmune events associated with juvenile idiopathic arthritis and found in the urine of over 80% of bladder cancer patients.…”
Section: Dek Regulates Chromatin Structure and Function In Normal Andmentioning
confidence: 99%
“…[28][29][30][31][32] During interphase, DEK plays a role in numerous nuclear processes including transcription, RNA processing, DNA repair, and chromatin organization. 20,[33][34][35][36][37] DEK is a highly modified protein, containing 57 potential phosphorylated sites and over 70 lysine residues with the potential to be poly ADPribosylated and ubiquitinated. 26,27,[38][39][40] Such modifications alter its ability to bind chromatin, re-localize, and carry out specific biological functions in a manner that remain poorly understood and have been studied primarily in cancer cells wherein DEK is over-expressed.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal DNA-binding region (residues 78-187) includes a SAF/SAP DNA-binding motif spanning residues 149-183. These residues are indeed responsible for mediating DEK's dsDNA-binding activity in the N-terminal region of , as shown by target bound assays (Bohm et al 2005). The SAF/SAP motif was originally identified within sequences of chromatin-associated proteins such as scaffold attachment factor A and B (Aravind and Koonin 2000;Kipp et al 2000).…”
mentioning
confidence: 97%
“…DEK's SAF/SAP homologous region has a 69% similarity with this consensus sequence, which indicates that DEK is loosely related to other proteins within this family. Furthermore, the SAF/SAP motif containing the N-terminal region of DEK (residues 68-226), is sufficient for the introduction of constrained positive supercoils into closed circular dsDNA (Bohm et al 2005).…”
mentioning
confidence: 99%